Arterial Stiffness, BMI, Dipping Status and ACE D/I Polymorphism in Type 1 Diabetic Children - Pietrzak, I.; Fendler, W.; Dróżdż, I.; Mianowska, B.; Młynarski, W.; Szadkowska, A. (Experimental and Clinical Endocrinology & Diabetes, 2016)
The aim: of the study was to investigate clinical and genetic determinants of arterial stiffness in children and adolescents with type 1 diabetes mellitus.Material and Methods: 122 patients (mean age: 16.0±2.35 years), with an average diabetes duration of 5.0 years and without evidence of arterial hypertension were recruited. Ambulatory arterial stiffness index (AASI) was assessed with 24-h automatic blood pressure monitoring. Body weight, height, HbA1c and plasma lipids were measured. Angiotensin I converting enzyme (ACE) gene insertion (I)/deletion (D) polymorphism was analysed.Results: Mean AASI equalled 0.22±0.20 and showed significant, positive correlation with age and BMI-SDS. No association was found between AASI and gender, diabetes duration, daily insulin dose, HbA1c and blood lipids concentration. AASI was higher in non-dippers compared to dippers (0.26±0.18 vs. 0.19±0.18, respectively; p=0.04). In a multivariate model AASI was significantly associated with II homozygosity of ACE gene (p=0.007).Conclusions: In type 1 diabetic children and adolescents AASI is correlated with age and BMI-SDS. Non-dipping status and I-allele were associated with higher arterial stiffness.
Keywords: diabetes; cardiovascular risk management; obesity